EFEKTIVITAS PEMBELAJARAN MATERI PEMBANGKIT LISTRIK DI KELAS VI SD: PERBANDINGAN ANTARA PEMBELAJARAN MELALUI MEMBACA DAN MENYIMAK VIDEO - Elpin, Agus; Maria S, Haratua Tiur; Karolina, Venny (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this research is to assess the effectiveness of two learning approaches, namely reading and watching videos, in increasing understanding the concept of electricity generation of sixth grade elementary school students. A comparison of two groups was carried out, namely the experimental group and the control group, each group consisting of 21 students. This comparison is based on their scores before and after the test. These findings show substantial improvement in the experimental group, measured by posttest scores ranging from 44 to 100 and a mean of 75.23. Meanwhile, the control group showed a lower increase, with posttest scores ranging from 28 to 68 and an average of 47.04. Mann-Whitney test analysis strengthened these findings by showing significant differences between the two groups (U= 49.500, Z= -4.399, Asymp. Sig= 0.001), with the experimental group consistently having higher ratings. Wilcoxon test findings in both groups also highlighted a significant improvement at posttest, with no decrease on scores from pretest. Overall, these results provide strong support for the effectiveness of the video listening method in improving student understanding compared to the reading method. This conclusion illustrates the importance of using inventive pedagogical approaches to improve students' academic achievement on science in the context of basic education.